Smart Packaging Innovation for Food: Enhancing Shelf Life and Quality of Perishable Goods - Rahman, Keisha Rafina; Ramdhani, Salzabila; Sanyoto, Viola Gracelia; Nawareza, Zheeva (ASEAN Journal for Science and Engineering in Materials, 2024)
Smart packaging has become a key factor in efforts to improve the shelf life and quality of perishable products. The purpose of this study is to analyze the importance of innovation in smart packaging to improve the shelf life and quality of perishable products. The research method used includes an in-depth literature study to gather relevant information to collect data on existing smart packaging innovations. To date, very few studies have been conducted specifically to discuss or propose innovative smart packaging development solutions to improve the shelf life and quality of perishable products. Hopefully, this paper can provide information on various new technologies and materials that can be used in smart packaging to extend the shelf life and maintain the quality of perishable products.